The monkey wrench gang - Abbey, Edward, 1927-1989 (Harper Perennial modern classics., 2006)
Ex-Green Beret George Hayduke returns from war to find his beloved southwestern desert threatened by industrial development. Joining with Bronx exile and feminist saboteur Bonnie Abzug, wilderness guide and outcast Mormon Seldom Seen Smith, and libertarian billboard torcher Doc Sarvis, M.D., Hayduke is ready to fight the power. They (the Monkey Wrench Gang) take on the strip miners, clear-cutters, and the highway, dam, and bridge builders who are threatening the natural habitat in this comedic novel of destructive mayhem and outrageous civil disobedience, which sparked the environmental activism movement. -- From back cover.